HEMATOLOGIS KAMBING KACANG JANTAN YANG DIBERI KULIT BUAH KAKAO SETELAH ALKALISASI DENGAN KOH DAN BIOFERMENTASI DENGAN Saccharomyces cerevisiae - Padang, Padang (AgriSains, 2011)
An experiment on processing cocoa pod by soaking it in KOH solution and fermenting it with Saccharomyces sereviceae was conducted to improve its nutrient quality and it effects on Kacang goat’s physiological responses. This study was carried out with a 2x4 factorially randomized design. The first factor was soaking treatment (soaked in KOH solution or not soaked), while the second factor was 4 levels of Saccharomyces cerevisiae concentration in diets (0, 5, 10, and 15%). Each treatment was repeated three times. Responses of soaking treatment on parameters observed were analyzed with a t test while those of Saccharomyces sereviceae levels were tested with            a polynomial orthogonal test. Results indicated that there were no interactions between the soaking treatment and concentration of Saccharomyces sereviceae in affecting the parameters observed. Concentrations of erythrocyte, hemoglobin, or hematocrit increased while that of leukocyte decreased with increasing levels of Saccharomyces sereviceae in diets. Soaking the cocoa pod in KOH solution decreased the number of leukocyte but it did not affect the numbers of erythrocyte, hemoglobin, or hematocrit. Key words: Cocoa-pod husk, fermentation, goat, KOH, physiological status.